2014
DOI: 10.1002/2014jc010246
|View full text |Cite
|
Sign up to set email alerts
|

Water mass analysis of the Coral Sea through an Optimum Multiparameter method

Abstract: A water mass analysis of the Coral Sea thermocline waters provides a description of their distribution, pathways and mixture based on recent oceanographic cruises in this region of strong western boundary currents. The Optimum Multiparameter method is used to determine the relative contribution of core water masses based on their measured temperature, salinity and dissolved oxygen. The thermocline waters, carried by the broad South Equatorial Current (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 44 publications
1
31
0
Order By: Relevance
“…Therefore, combined with the results of mass balance residuals and Monte Carlo analysis, the typical error solution was considered to be10%. This error level is close to that considered in the water mass analysis of the Coral Sea using an OMP method (Gasparin et al, ).…”
Section: Optimum Multiparameter Methodssupporting
confidence: 83%
See 1 more Smart Citation
“…Therefore, combined with the results of mass balance residuals and Monte Carlo analysis, the typical error solution was considered to be10%. This error level is close to that considered in the water mass analysis of the Coral Sea using an OMP method (Gasparin et al, ).…”
Section: Optimum Multiparameter Methodssupporting
confidence: 83%
“…The full solution of the OMP analysis is then found by minimizing: normalRTnormalR=|normalGnormalXnormaldTW1true(normalGnormalXnormaldtrue) where G is the SWT definition matrix as shown in Table ; T is the transposed matrix operator; and W −1 is the diagonal weight matrix W (= ω 2 I , where I is the identity matrix). Each equation is weighted by the standard deviation ω of each property as in previous studies (Gasparin et al, ; Maamaatuaiahutapu et al, ). The resulting T, S, and mass conservation equations are assigned a much higher weight than the DIIS.…”
Section: Optimum Multiparameter Methodsmentioning
confidence: 99%
“…In the WEP, SPTW can further be divided into two branches, one branch reaching the Solomon Sea via the NVJ (Germineaud et al, ; Grenier et al, ), and a second branch entering the Solomon Sea via the GBRUC (Gasparin et al, ). WSPCW forms seasonally through winter‐convection in the subtropical convergence zone between Tasmania and New Zealand (Grenier et al, ; Roemmich & Cornuelle, ; Qu et al, ) and reaches the southern study site via the NCJ and GBRUC (Gasparin et al, ). Below the thermocline, SAMW‐density water (26.8–27.1σ θ ) is discernible as a pycnostad with relatively high oxygen concentrations and a characteristically low silicate‐to‐nitrate ratio (Si* minimum; Sarmiento et al, ).…”
Section: Study Areamentioning
confidence: 99%
“…The eastward surface current flowing south of NC is called the SubTropical CounterCurrent (STCC); Ridgway and Dunn (2003) showed that this surface current is not continuous but occurs as a series of branches that emanate from the East Australian Current recirculation and flow toward or south of the main land of NC (see their Salinity is a useful parameter to trace water masses, and is used as a complementary tool to follow current pathways. The water masses' properties entering the Coral Sea have been described in detail (see for example Tomczak and Hao, 1989;Lindstrom, 2002, 2004;Qu et al, 2009;Grenier et al, 2013Grenier et al, , 2014Kessler and Cravatte, 2013a;Ganachaud et al, 2014;Gasparin et al, 2014), and for the purpose of this study, only a few points of their findings need to be reminded. Two distinct thermocline water masses originating from different subduction zones enter the Coral Sea at different densities.…”
Section: Background: Large-scale Circulation and Water Masses In The mentioning
confidence: 99%